Global and Regional Estimates of Prevalent and Incident Herpes Simplex Virus Type 1 Infections in 2012 - Looker, Katharine J.; Magaret, Amalia S.; May, Margaret T.; Turner, Katherine M. E.; Vickerman, Peter; Gottlieb, Sami L.; Newman, Lori M. (PloS one, 2015)
Herpes simplex virus type 1 (HSV-1) commonly causes orolabial ulcers, while HSV-2 commonly causes genital ulcers. However, HSV-1 is an increasing cause of genital infection. Previously, the World Health Organization estimated the global burden of HSV-2 for 2003 and for 2012. The global burden of HSV-1 has not been estimated. We fitted a constant-incidence model to pooled HSV-1 prevalence data from literature searches for 6 World Health Organization regions and used 2012 population data to derive global numbers of 0-49-year-olds with prevalent and incident HSV-1 infection. To estimate genital HSV-1, we applied values for the proportion of incident infections that are genital. We estimated that 3709 million people (range: 3440-3878 million) aged 0-49 years had prevalent HSV-1 infection in 2012 (67%), with highest prevalence in Africa, South-East Asia and Western Pacific. Assuming 50% of incident infections among 15-49-year-olds are genital, an estimated 140 million (range: 67-212 million) people had prevalent genital HSV-1 infection, most of which occurred in the Americas, Europe and Western Pacific. The global burden of HSV-1 infection is huge. Genital HSV-1 burden can be substantial but varies widely by region. Future control efforts, including development of HSV vaccines, should consider the epidemiology of HSV-1 in addition to HSV-2, and especially the relative contribution of HSV-1 to genital infection.